Review of Comsoft Aeronautical Data Access System Information Management & Service in the NOTAM Flow at Palembang Regional Aeronautical Information Service - Puspa Aryani, Dian; Sadiatmi, Rini; Saulina, Martha (Journal Innovations Computer Science, 2025)
This study aims to describe how the Comsoft Aeronautical Data Access System (CADAS) is used in the NOTAM workflow at Palembang Aeronautical Information Service and how operators behave when the system is not stable. This research was conducted with a qualitative case study approach, which combined interviews, participatory observations, and document analysis to capture daily operational practices and problems that occurred in real conditions. The results of this study indicated that CADAS is still the main system for NOTAM drafting, verification, and transmission. However, its performance is often disturbed by irregular system errors such as sudden shutdowns, delays in data processing, and intermittent failures to send or receive raw NOTAM information. These disturbances create obstacles in fulfilling time-sensitive procedural requirements especially the ten-minute verification standard as stated in SOP.012. In case of system unresponsiveness, operators switch to alternative procedures through email distribution, Web Flight Plan submission, and manual logbook documentation so as not to cause delays; however, these manual steps require continuous follow-up to avoid gaps in recording. In general, this study underlines the importance of increasing CADAS reliability and ensuring that backup procedures are consistently applied so that continuity can be maintained even if there is an interruption in the system.